Dynamic voltage restorer (DVR) enhancement in power quality mitigation with an adverse impact of unsymmetrical faults - Farooqi A.; Othman M.M.; Radzi M.A.M.; Musirin I.; Noor S.Z.M.; Abidin I.Z. (Elsevier Ltd, 2023)
Electric power transmission networks; Power quality; Steel beams and girders; Transient analysis; Voltage regulators; Distribution lines; Dynamic voltage restorers; Grid systems; Microgrid; Photovoltaic grids; Power systems stability; Quality issues; Renewable energies; Severe weather; Unsymmetrical faults; Energy efficiency